2018
DOI: 10.1029/2018jb015801
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Rifts in Central Tibet: Insight From P Wave Radial Anisotropy

Abstract: The strikes of rifts in western Tibet show NNW‐SSE trending, whereas the rifts in eastern Tibet strike in the NNE‐SSW direction. The difference in the rift strike orientation suggests that the formation mechanisms of these rifts are different in southern Tibet, which can be most reliably inferred from seismic structure beneath these rifts. In this work we study 3‐D P wave velocity structure and radial anisotropy using a large number of travel time data recorded by the ANTILOPE and Hi‐CLIMB portable seismic arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…A magnetic and gravity study revealed that the whole WSB is underlain by a rifted continental crust (Ferraccioli et al, 2009). The rifting can raise the temperatures and change the anisotropic features not only in the crust but also in the upper mantle (Savage , 1999 ; Zhang et al, 2018). At the western edge of the WSB (near the Belgica Highlands), SWS results reveal different fast directions from those in the NTAM (Barklage et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A magnetic and gravity study revealed that the whole WSB is underlain by a rifted continental crust (Ferraccioli et al, 2009). The rifting can raise the temperatures and change the anisotropic features not only in the crust but also in the upper mantle (Savage , 1999 ; Zhang et al, 2018). At the western edge of the WSB (near the Belgica Highlands), SWS results reveal different fast directions from those in the NTAM (Barklage et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the HVZ with a negative RAN feature in the northern part of the profile (H1' in Figure 3a) reflects that the northern part of the ILM was affected by the previously attached Tethyan oceanic slab (H. Zhang et al, 2018) because the negative RAN anomaly is generally related to vertical shear or deformation. Another interpretation of the HVZ is foundering ILM.…”
Section: Different Deformation Patterns Within the Ilmmentioning
confidence: 97%
“…Another controversial issue is whether the formation of the Tibetan rifts (or grabens) is a crustal process or related to the whole lithosphere or the asthenosphere (Yin & Harrison, 2000). Most of the seismic studies prefer the latter case, including slab tearing in the ILM (X. F. Liang et al., 2016), internal deformation of the ILM and ELM (H. Zhang et al., 2018), and upwelling asthenosphere (Ren & Shen, 2008). However, such seismic evidence depends on the limited data recorded by seismic arrays in central and eastern Tibet.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous workers have studied the crustal and upper mantle structure under western Tibet with receiver functions, tomography, and shear wave splitting (Li et al, 2008;Nabelek et al, 2009;Chen et al, 2010;Hung et al, 2010;Xu et al, 2011;Basuyau et al, 2013;Zhang et al, 2012Zhang et al, , 2015Zhang et al, , 2018Liang et al, 2016;Wang et al, 2019). However, most of these studies utilize the seismic data recorded by Hi-CLIMB Project from southern to central Tibet plateau, whereas little research has been conducted in the northern Tibet.…”
Section: Introductionmentioning
confidence: 99%